EVALUATING THE IMPLEMENTATION OF PSAK 109 IN ZAKAT, INFAQ, AND SADAQAH ACCOUNTING: EVIDENCE FROM LAZISMU LHOKSEUMAWE - Mardiaton; Ayu Sri Ningsih; Nur Afni Yunita; Irne Aryanie; Cut Sri Firman Hastuti (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study analyses the implementation of zakat, infaq, and sadaqah (ZIS) accounting in accordance with PSAK 109 at LAZISMU Lhokseumawe. PSAK 109 governs the recognition, measurement, presentation, and disclosure of ZIS transactions to ensure transparency and accountability in the management of public funds. The research applies a qualitative case study approach, using interviews, observations, and document analysis. The findings indicate that the implementation of PSAK 109 at LAZISMU remains incomplete. Recognition and measurement of ZIS funds are mostly in line with the standard, as receipts and distributions are recorded by category. However, significant weaknesses remain in presentation and disclosure. Financial reports are limited to receipts and disbursements, without statements of financial position, cash flows, or explanatory notes as required by PSAK 109. These results highlight the need to strengthen human resource capacity, adopt digital accounting systems, and enhance the role of the Sharia Supervisory Board so that financial reporting can be more transparent, accountable, and fully compliant with PSAK 109 and Islamic governance principles.